Adult Onset Nesidioblastosis (Non Insulinoma Pancreatogenous Hypoglycemia Syndrome): A Rare Case - Rita Sriwulandari; Yulianto Kusnadi; Ratna Maila Dewi; Alwi Shahab; Anne Rivaida (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Finding the etiology of hypoglycemia in adult patients can be challenging because of the wide variety of etiologies. Ninety percent of endogenous hyperinsulinemic hypoglycemia is caused by insulinoma, the rest are caused by insulin antibodies and pancreatic β cell dysfunction (nesidioblastosis) which indicates neoformation of nesidioblasts (stem cells that form the islets of Langerhans). A 28-year-old female complained of neuroglycopenia and adrenergic symptoms that improved with drinking sugar, so she had weight gain. The 72 hours of prolonged fasting test results are C-peptide ≥0.2 mmol/L, insulin ≥21 pmol/L, insulin to C-peptide molar ratio ≤1, and negative insulin antibody. Imaging tests were normal and there is no evidence of malignancies. When blood glucose falls, the first defense mechanism to prevent hypoglycemia is decreased in insulin secretion. When this mechanism fails, insulin and C-peptide levels remain high in circulation. Confirmation of Whipple's triad is required, followed by insulin tests in hypoglycemic conditions. Imaging tests, biomarkers, and hormonal malignancies were done to rule out differential diagnoses. Nuclear diagnostics, SACST, biopsy, and histopathology are currently in capable of being carried out. The diagnosis of adult-onset Nesidioblastosis/NIPHS in this patient was made through the diagnosis of exclusion, namely by eliminating all diagnostic appeals because several examination modalities cannot be carried out. The gold standard for diagnosing Nesidioblastosis/NIPHS is SACST and histopathological examination of pancreatic tissue. The patient is well-controlled with Amlodipine 2.5 mg.